Netnography Analysis : Digital Society's Perception of The Influence of Local Revenue on The Development of Palu City - Selvyana; Karim, Fikry; Meldawati, Lucyani; Masruddin (Equivalent : Journal of Economic, Accounting and Management, 2025)
The study aims to determine perceptions among the people of Palu city on Intagram@palu.kota posts related to news uploads and people's perceptions in the comments column regarding the development of the Palu City Region, social media which are the most frequently visited pages, namely Instagram@palu.kota, and Tiktok@Info Palu. In depth, we conducted this research to analyze the impact of uploads in the social media platform on Public Perceptions related to the Regional Development of Palu City with a qualitative approach with the netnography method because this method makes it easier for the author to analyze the perceptions or comments of the digital community on social media as a source of data for this research. We made this research to understand how much influence the level of concern of the digital community of Palu City to find out the utilization and use of PAD funds in the development of Palu City through content analysis interactions in online media forums related to the issue of Palu City Development. The results showed that users of social media forums including Instagram and tiktok are increasingly varied in giving comments both containing positive or negative assessments to the Palu City Regional government in Regional Development, especially in the Public area.The conclusion of this article is that a better understanding of the perceptions of digital communities can help the government in designing policies that are more effectively accepted by digital communities by involving them in the dialogue and decision-making forums of the Palu City Regional government so that they can run more effectively and sustainably.This research also contributes to the literature on netnography and digital community participation in the context of Regional Development.